2006
DOI: 10.1071/bt05046
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of tree plantations on groundwater in south-eastern Australia

Abstract: In some regions dependent on groundwater, such as the lower south-east of South Australia in the Green Triangle, deep-rooted, woody vegetation might have undesirable hydrological impacts by competing for finite, good-quality groundwater resources. In other regions, such as the Riverina in south-central New South Wales, where rising watertables and associated salinisation is threatening the viability of agriculture, woody vegetation might have beneficial hydrological impacts. In response to a growing need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
183
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(223 citation statements)
references
References 22 publications
11
183
2
4
Order By: Relevance
“…Pan evaporation rates can be used instead of ET p , in which case ET p = 0.75 E pan . Modest agreement between modelled and observed rates of groundwater discharge was found in two Australian studies where ET exceeded rainfall in the Wattle Range by 2 to 440 mm yr −1 (Benyon and Doody, 2004), although the range of estimated groundwater discharge rates was large: 107 to 671 mm yr −1 (Benyon and Doody, 2004) and 380 to 730 mm yr −1 (Benyon et al, 2006).…”
Section: Eamus Et Al: Groundwater-dependent Ecosystems: Recent Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Pan evaporation rates can be used instead of ET p , in which case ET p = 0.75 E pan . Modest agreement between modelled and observed rates of groundwater discharge was found in two Australian studies where ET exceeded rainfall in the Wattle Range by 2 to 440 mm yr −1 (Benyon and Doody, 2004), although the range of estimated groundwater discharge rates was large: 107 to 671 mm yr −1 (Benyon and Doody, 2004) and 380 to 730 mm yr −1 (Benyon et al, 2006).…”
Section: Eamus Et Al: Groundwater-dependent Ecosystems: Recent Inmentioning
confidence: 99%
“…Although we cannot pinpoint the exact breakpoint with precision, it is clearly apparent that a breakpoint does occur in the data. Furthermore, two recent reviews based on water balance concluded that groundwater uptake ceased when depths exceeded 7.5 m (Benyon et al, 2006) The solute potential at a relative water content of 100 % RWC TLP The relative water content at which leaf turgor is zero SWD The saturated water content of wood K s Sapwood-specific hydraulic conductivity of branch xylem K L Leaf-specific hydraulic conductivity of branch xylem PLC 50 The water potential at which 50 % of the hydraulic conductivity is lost PLC 88 The water potential at which 88 % of the hydraulic conductivity is lost H v Huber value: the ratio of leaf area to sapwood area BA Total basal area of trees within a plot LAI Leaf area index of a stand of trees AGB Above-ground biomass ANPP Above-ground net primary productivity WUE Water-use efficiency; calculated as the ratio of ANPP/stand water use Height Average height of the trees in a plot Water use…”
Section: Multiple Traits Across Leaf Branch Whole-tree and Standmentioning
confidence: 99%
“…direct evaporation from the canopy and stem, usually estimated as the difference between rainfall and throughfall), E = evaporative losses from the soil surface (usually measured with mini lysimeters), T = transpiration (measured directly e.g. using sapflow techniques) and S w is the change in the volumetric soil water content between two time periods (Benyon et al, 2006). All the studies included in this review were plot scale water balance studies, conducted for a period of at least 12 months, where evapotranspiration was calculated as the sum of E, T and I .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years there has been increasing recognition of the role that groundwater plays in the maintenance of ecosystem structure and function (Eamus and Froend, 2006). Groundwater use has been demonstrated in a range of terrestrial vegetation communities around Australia including woodlands in Mediterranean environments (Groom, 2000), riparian ecosystems (Thorburn et al, 1993;Lamontagne et al, 2005), temperate plantations (Benyon et al, 2006), tropical and arid woodlands and tropical forests (Drake and Franks, 2003;O'Grady et al, 2006O'Grady et al, , 2009. Recognition of the importance of this water resource to vegetation functioning imposes an imperative on water Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…Increased annual ET from afforestation of grasslands or cropping areas is generally observed (e.g. Zhang et al, 2001;Benyon, 2002;Benyon et al, 2006), resulting in decreased stream flow (Bosch and Hewlett, 1982;Bubb and Croton, 2002;Best et al, 2003). As pointed out by Lane et al (2005), the impacts of changing land use on the total flow regime and flow duration curves is less well understood with some of their studied catchments showing a greater increase in zero-flow days after afforestation, while another group shows a more uniform reduction in flows across all flow duration percentiles.…”
Section: Study Locationmentioning
confidence: 99%